The making of Malaysian solidarity: a historical look at education and social cohesion in Sarawak - Ong, Puay Liu; Ong, Puay Hoon; Sivapalan Selvadurai; Marsitah Mohd Radzi; Badariah Saibeh (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
In a multi-ethnic, multicultural and multi religious country like Malaysia an education system that promotes inclusion and participation of all citizens, where diversity of learners is recognised and acknowledged would certainly enhance national solidarity. Such an inclusive education, which aspires to promote social cohesion through greater understanding, respect and interactions among students, may be grounded on the four principles/pillars of learning to know, learning to do, learning to be and learning to live together. The demographic plurality of Malaysia which consists of the 11 states in Peninsular Malaysia, and the states of Sabah and Sarawak on the island of Borneo calls for this inclusive education system. How much do Malaysians know about one another? In particular, how much do Malaysians from Peninsular Malaysia know about their fellow citizens in Sabah and Sarawak, and vice versa? Sarawak, being the only state in Malaysia ruled by ‘white Rajahs’ for about a century, offers an interesting opportunity to see whether the education system evolved has promoted inclusion and social cohesion within itself as well as within the larger Malaysian society. By analysing the history of Sarawak education, beginning with the Brooke rule from 1841 to 1946, and continuing to the British administration from 1946 to 1963 this article concludes that social cohesion beyond inter-ethnic boundaries was not considered an important agenda during the Brooke as well as the British administrations thus leaving the present government with the ongoing monumental task of effectively utilising education in the making of the Malaysian solidarity .